Credibility Crisis among Agriculture Extension Functionaries in Jammu and Kashmir - Slathia, P.S.; Paul, Narinder; Nain, M. S.; Nanda, Rakesh; Peshin, R. (Indian Journal of Extension Education, 2012)
The present paper focuses on the factors, which have led to the loss of credibility of the extension workers in Jammu and Kashmir and explore the ways and means to strengthen the credibility of the extension workers so that they would efficiently work at grass-root levels. To achieve the objectives of the study, 120 Junior Agriculture Assistants (JAAs) of Department of Agricultural Production rendering their services at different locations of the state were interviewed, and responses taken of a specially designed instrument. It was found that the main factors, which have led to the loss of credibility among the extension functionaries, are improper technologies fed to the extension delivery system, involvement of extension workers in irrelevant administrative works, improper training imparted to the field extension functionaries in technology transfer methodologies, improper methods of presenting information, little cooperation from subject matter specialists, concept of salesman ship among the private sector representatives to achieve their targets etc. The representatives of different seeds and pesticide companies are misleading farmers for a short time to achieve their targets by providing them hollow promises of high yields. In short run, they managed to mislead farmers but in long run the credibility of other extension worker gets eroded as farmers recall their past bitter experiences with the extension workers. Besides, illiteracy among farmers, lack of trailability among the farmers, preponderance of below-standard products in the market, involvement of extension workers in many financial and credit schemes, promotion of the professionally less qualified personnel to the rank of extension professionals who do not have the required skills of dealing with the farmers also found to affect the credibility of the field extension functionaries. It was found that maintaining trust among the farming community requires induction of professionally qualified personnel and their regular trainings. We have to see that the credibility of the extension worker is maintained and the crisis through which the extension functionary of the day is passing is overcome. It was concluded that to overcome the credibility crisis among the extension functionaries, the factors mentioned above must be taken seriously and work should be planned and implemented to address these crucial issues if the extension is to deliver goods in the days to come.